Who Gets Included? Examining Socioeconomic Determinants of Digital Financial Inclusion in Indonesia Using a Probit Model - Aris Munandar (International Journal of Management, Economic and Accounting, 2026)
This study examines the effect of socioeconomic factors on digital financial inclusion in Indonesia using individual-level data from 1,068 respondents from the Global Findex 2025. Using probit regression, the analysis divided digital financial inclusion into accessibility and usage. The results revealed a two-stage pattern of inclusion. Access to digital financial services, such as debit cards and mobile money, is primarily driven by age, education, workforce participation, and income, with younger, more educated, participating in the workforce, and higher-income individuals showing higher access. In contrast, usage is dominated by income, as the highest quintile consistently predicts the active use of most digital financial services. Age emerges as a persistent barrier to both access and usage, reflecting deep generational gaps in digital literacy. Urban residence only becomes significant at the usage stage, indicating geographic concentration in service delivery. Gender inequality is narrowly limited to credit card access and does not extend to broader usage patterns. Workforce participation drives account opening more than active financial engagement. These findings underscore that Indonesia faces a two-stage inclusion challenge: expanding access requires addressing educational and labor market barriers, while deepening usage demands income growth policies and targeted digital literacy interventions, particularly for older and rural populations.